2018
DOI: 10.1080/2162402x.2017.1395997
|View full text |Cite
|
Sign up to set email alerts
|

Intra-tumoral delivery of CXCL11 via a vaccinia virus, but not by modified T cells, enhances the efficacy of adoptive T cell therapy and vaccines

Abstract: T cell trafficking into tumors depends on a "match" between chemokine receptors on effector cells (e.g., CXCR3 and CCR5) and tumor-secreted chemokines. There is often a chemokine/chemokine receptor "mismatch", with tumors producing minute amounts of chemokines, resulting in inefficient targeting of effectors to tumors. We aimed to alter tumors to produce higher levels of CXCL11, a CXCR3 ligand, to attract more effector cells following immunotherapy. Mice bearing established subcutaneous tumors were studied. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 48 publications
1
77
1
Order By: Relevance
“…Additionally, OVs can be engineered to express immunostimulatory molecules (e.g., chemokines, cytokines, and bispecific T-cell engagers) to better enhance the antitumor activity of CAR T cells. This strategy has been investigated in different solid tumor types, leading to the improved survival of tumor-bearing mice [ 120 , 121 , 122 , 123 , 124 ]. However, the synergistic effects of OVs and CAR T cells in the context of brain tumors remain to be tested.…”
Section: Combination Therapy In Preclinical and Clinical Settingsmentioning
confidence: 99%
“…Additionally, OVs can be engineered to express immunostimulatory molecules (e.g., chemokines, cytokines, and bispecific T-cell engagers) to better enhance the antitumor activity of CAR T cells. This strategy has been investigated in different solid tumor types, leading to the improved survival of tumor-bearing mice [ 120 , 121 , 122 , 123 , 124 ]. However, the synergistic effects of OVs and CAR T cells in the context of brain tumors remain to be tested.…”
Section: Combination Therapy In Preclinical and Clinical Settingsmentioning
confidence: 99%
“…June's group [182] reported that oncolytic adenovirus expressing TNF-α and IL-2 robustly increased meso-CAR T cell and host T cell infiltration into the tumor, overcame the immunosuppressive TME, and increased the DC maturation; these results indicate that combining with cytokine-expressing OVs can enhance the efficacy of CAR T cell therapy in solid tumors. Studies have also examined the ability of chemokine-expressing OVs in CAR T cells; a modified oncolytic vaccinia virus expressing CXCL11 successfully recruited T cells and significantly enhanced the anti-tumor efficacy of meso-CAR T cells [183]. This finding was further demonstrated by Dotti et al, who combined CAR GD2-T cells with OVs expressing the chemokine RANTES and cytokine IL-15, facilitating the migration and survival of CAR T cells and increasing their overall anti-tumor activity in tumor-bearing mice.…”
Section: Combination With Oncolytic Virotherapymentioning
confidence: 99%
“…Oncolytic adenoviruses modified to express IL-15 and RANTES ( 87 ) or IL-2 and TNF-α ( 88 ) have been shown to increase the accumulation and survival of CAR-T cells in the tumor microenvironment. Similarly, with the goal of enhancing the intra-tumoral trafficking of CAR-T cells, a vaccinia virus expressing CXCL11, a CXCR3 ligand, was used to attract effector cells following transfer ( 89 ). Another report demonstrated that expression by an oncolytic adenovirus of a BiTE targeting a second tumor antigen could address heterogeneity of antigen expression ( 40 ).…”
Section: Oncolytic Viruses: the Ideal Allies For Car-t Cells?mentioning
confidence: 99%